2006
DOI: 10.1021/nl062419e
|View full text |Cite
|
Sign up to set email alerts
|

Columnar Self-Assembly of Colloidal Nanodisks

Abstract: The self-assembly of sterically stabilized colloidal copper sulfide nanodisks, 14-20 nm in diameter and 5-7 nm thick, was studied. The nanodisks were observed by electron microscopy and small-angle X-ray scattering to form columnar arrays when evaporated as thin films from concentrated dispersions. These superstructured nanomaterials might give rise to technologically useful properties, such as anisotropic electrical transport and electrorheological and optical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
108
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(118 citation statements)
references
References 66 publications
10
108
0
Order By: Relevance
“…Therefore, we reasoned that the capping ligand (i.e., Sn À X complex), the intrinsic anisotropic structure of Cu 2 S, and van der Waals attraction had cooperative effects on the formation of the self-assembled Cu 2 S hexagonal nanoplates. [31][32][33][34] Based on the above observations and analyses, it was found that the formation of 1D arrangements was preferred as particles stacked in a face-to-face configuration by maximizing ligand-surface interactions (MLSI). Then, the high ligand density along the side of a 1D columnar arrangement could further induce well-defined 2D raftlike and 3D stratiform self-assembly ( Figure S5 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we reasoned that the capping ligand (i.e., Sn À X complex), the intrinsic anisotropic structure of Cu 2 S, and van der Waals attraction had cooperative effects on the formation of the self-assembled Cu 2 S hexagonal nanoplates. [31][32][33][34] Based on the above observations and analyses, it was found that the formation of 1D arrangements was preferred as particles stacked in a face-to-face configuration by maximizing ligand-surface interactions (MLSI). Then, the high ligand density along the side of a 1D columnar arrangement could further induce well-defined 2D raftlike and 3D stratiform self-assembly ( Figure S5 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The mean interlayer distance was found to be 6.4 nm. The mesoscale structure of the thin films was probed using grazing-incidence small-angle X-ray scattering (GISAXS) 30,31 . The alignment of 2D crystals can be determined by the location of the interference peaks on the x-z plane of the 2D diffractogram.…”
Section: Spray-coatable Oligomer-tethered Nanoplateletsmentioning
confidence: 99%
“…The formation of columnar superstructures has been reported for gibbsite [1] and copper sulfide platelets. [2] Beautiful iridescent liquid-crystalline phases (nematic or smectic) have been reported for suspensions of rodlike particles, including DNA, [3] viruses, [4] BaCrO 4 , [5] b-FeOOH, [6] TiO 2 , [7,8] and CdSe. [9] Semiconductor nanorods with interesting optical properties are useful for device applications (light-emitting diodes, memory devices, and solar cells), and efforts have been made to produce large-area ordered semiconductor nanorod superstructures.…”
mentioning
confidence: 99%